Sorting Master - Taima Hamadneh; Areen Jawabrh (My University, 2023)
Certain industries face challenges in efficiently categorizing and organizing goods based on their country of manufacturing. Because it takes more time and effort, this frequently results in an increase in operational stress, which may lead to lower productivity and a lack of streamlined operation. The ”Sorting Master” proposed by our concept aims to solve this issue by providing a sorting machine. This device improves the classification procedure by offering a system for classifying goods according to their geographic location of manufacturing. The sorting machine decreases human error in the sorting process while also improving operational efficiency by automating this process. Furthermore, Sorting Master addresses the challenges of categorizing goods by manufacturing country by providing an innovative and efficient solution.Automation increases productivity and lowers error rates. This technology has the power to transform whole industries, increasing overall productivity and streamlining operations. 6